Effect Artificial Rice Diet Administration to Coronary Artery Histopathology of Rat Model Type 2 DM - Monika Roosyidah; Erfan Efendi; Hairrudin Hairrudin (Journal of Agromedicine and Medical Sciences, 2017)
The most common macrovascular complication of type 2 DM’s patiens is coronary artery disease caused by coronary artery stricture or spasm or both of them. The atherosclerosis process in coronary artery can be seen through coronary artery histopathology of rat. DM can be controlled so that the complication can be prevented, for example by controlling diet. Artificial rice with high fiber is one of breakthrough for DM patients diet. The purpose of this research is to know about the effects of artificial rice diet administration to coronary artery histopathology of rat model type 2 DM. Rats are divided to four groups consist of control normal group given standart feeding, PBA1;PBA2;PBB group are inducted by high fat diet and low dose STZ so that they become rat model type 2 DM. Since PBA1 is feeded by formula 1 artificial rice, PBA1 is feeded by formula 2 artificial rice and PBB is feeded by common rice. Rats are terminated and their hearts are taken away to make histopathology object and their coronary artery are seen under light microscope. Histopathology images are based on foam cell formed. Kruskal-Wallis’s result shows that p= 0,046 (p<0,05), so that there is a significant difference between groups.Keywords : DM, atherosclerosis, foam cell, coronary artery histopathology